Pembuatan sediaan beads alginat dengan metode gelasi ion yang dapat mengapung di lambung - Nur Adliani (Journal of Science and Applicative Technology, 2017)
Conventional drug delivery systems have a shorter residence time in the stomach that causes less optimal drug absorption, the presence of food in the stomach also affects the absorption of the drug in the gastrointestinal tract so that it takes a drug that can stay and last longer in the stomach without being affected by the emptying process Stomach. In this study beads preparations are made that can stay and float so that lasts longer in the stomach. Alginate-containing beads are formulated by gelation method in which the alginate solution is dropped into a calcium chloride solution to form beads. The effects of oil type and alginate on morphological forms and buoyancy characteristics have been optimized. Beads containing alginate and paraffin can float on a gastric medium simulation for 240 minutes. The presence of paraffins can maintain the integrity and release of alginate beads during contact with the gastric medium. The SEM results describe the paraffin forming globules on the entire surface of the beads. Beads also show the ability to be able to float depending on the concentration of paraffin used.